Maqāṣid as Evaluative Rationality for the Incorporation of International Norms into the Constitutional Structure - Arie E Baskoro; Adhe Ismail Ananda; Lidya Potts; La Ode Dedihasriadi (Al-'Adl, 2026)
Legal globalisation has led to increasingly complex relations between international law and national constitutional systems, particularly in the context of countries with plural legal systems and religious value foundations. This study highlights the urgency of developing a conceptual model capable of integrating international legal norms into the national legal structure without negating constitutional principles and maqāṣid al-sharī‘ah values. The main objective of this study is to examine maqāṣid as an evaluative paradigm in assessing the legitimacy of international norms within a constitutional framework. Using a normative-doctrinal method enriched by a comparative approach to legal systems and maqāṣid-based interpretation, this study formulates a triadic model of harmony between international legality, constitutional principles, and maqāṣid values. The findings show that the maqāṣid approach is not only relevant as Islamic normative ethics, but can also function as a conceptual instrument in constitutional testing of global norms. The proposed triadic harmonisation model consists of three layers of evaluation: legality, constitutional legitimacy, and public interest. Through a maqāṣid value structure that encompasses the protection of religion, life, intellect, property, and lineage, international norms can be filtered rationally and contextually. Theoretically, this research broadens the horizons of Islamic constitutionalism in responding to global legal dynamics. Practically, this model can be used by policymakers and judicial institutions in assessing the compatibility of global norms with national legal identities rooted in substantive justice.